A taxonomic and phylogenetic perspective on plant community assembly along an elevational gradient in subtropical forests. (26th March 2021) - Zhang, Ran; Zhang, Zhaochen; Shang, Kankan; Zhao, Mingshui; Kong, Jiaxin; Wang, Xin; Wang, Yuzhuo; Song, Houjuan; Zhang, Oukai; Lv, Xuan; Zhang, Jian
Abstract: Aims: Biodiversity patterns along elevational gradients have been well documented. Yet, the variations of biodiversity patterns along elevations and their underlying mechanisms are still unclear. Integrating multiple facets of biodiversity provides novel insights into the mechanisms for driving community assembly. In this study, species abundance information was incorporated into taxonomic and phylogenetic diversity to reveal the ecological and evolutionary forces of plant community assembly along an elevational gradient in subtropical forests. Methods: We selected 17 woody plant plots along an elevational gradient from 270 to 1470 m in eastern China's subtropical forests. Both presence-based and abundance-based measures of angiosperm species were used to quantify taxonomic alpha diversity, phylogenetic alpha diversity, phylogenetic relatedness, as well as taxonomic and phylogenetic dissimilarity among these plots. And the relations between these measures and climatic and topographic variables were analyzed. Important Findings: For both abundance-weighted and unweighted measures, we observed an overall increasing pattern for taxonomic alpha diversity along elevation, and distance-decay trends of taxonomic and phylogenetic similarity with increased elevational distances. However, there were disparity patterns of phylogenetic alpha diversity between abundance-weighted and unweighted measures. For phylogenetic structure, there was no significant trend along elevation. Both topographical and microclimatic variables were main drivers of diversity patterns and phylogenetic structure. Compared with unweighted measures, abundance-weighted measures were strongly related with the slope and stand basal area. Overall, our results prove that deterministic processes mediated by local species abundance imprint on plant community composition along the elevational gradient.